Design and Simulation of Switched Capacitor Based Multilevel Inverter with Reduced Components - Rohith G B; Dr. Jagadisha K R (International Journal of Engineering and Management Research, 2023)
Function of inverter is to convert DC signal to AC signal. Boost voltage and to improve the power quality and capacity with sinusoidal type waveform is obtained by use of multi-level inverter. The Multilevel inverter increases number of devices and other components, switched-capacitor (SC) units have ability to boost the input voltage considerably switched capacitor-based inverter with reduced switch is proposed in this paper without inductor and transformer operation with voltage boosting feature and inherent capacitor self-voltage balancing performing with no interference. The structure proposed in this paper is capable of producing 17 level output waveform with double voltage gain using a dual voltage source with reduced switches and other equipment’s. The inverter switching pulse is modulated using PD-PWM technique, which enables a high quality output waveform.